ASIMILASI DAN KONTRAS DALAM BRAND DAN EVALUASI PRODUK : IMPLIKASI UNTUK PEMASARAN - Euis Eka Pramiarsih (Lembaga Penelitian, Publikasi dan Pengabdian pada Masyarakat (LP3M) Nobel Indonesia, 2017)
This study describes a framework according to which the same piece of information may elicit assimilation or contrast in the evaluation of a target. Thus, a brand extension may either help or hurt the brand and vice versa, a top-of-the-line product may increase or decrease the attractiveness of other models of the product line. Whether contrast or assimilation occurrs is not solely determined by the features of the stimuli as other models would predict. We show how marketing strategies may moderate the impact of a stimulus and determine whether, for example, the top-of-the-line-model helps or hurts its younger siblings. That the perception and evaluation of stimuli is influenced by the context in which we perceive and evaluate them is common knowledge and almost trivial. What makes context effects, nevertheless, interesting is that contextual influences may take quite opposite forms. For example, we may wonder whether an average car looks more expensive when displayed in a range of up-scale cars or whether it looks cheaper. The former assimilation effect, a shift in the evaluation of a target towards the context evaluation, may be plausible (among other accounts) because we perceive the target car as part of the range. The latter contrast effect, a shift in the evaluation of the target away from the context evaluation, may be plausible because the up-scale range provides a standard of comparison against which the target car looks less posh. Clearly, the question that has been intriguing psychologists and other scholars alike is: What determines whether a context stimulus elicits assimilation or contrast in a target evaluation? The present paper gives a very short review of the basic mechanisms underlying assimlation and contrast effects (for a more detailed review see Schwarz & Bless, 1992a). Following this, we will present an overview of several studies in the marketing domain, which demonstrate how marketers can use these basic processes in order to elicit specific brand or product evaluations.